Chemical synthesis of single nanometer-sized Bi2−xSbxTe3.0 nanocrystals via direct precipitation process - Ryosuke Fujiwara; Yohei Takashima; Takaaki Tsuruoka; Muneyuki Naito; Junya Murai; Kensuke Akamatsu (Results in Chemistry, 2022)
The synthesis of high-purity nanocrystals as precursors is important to fabricate nanostructured thermolectronics with high thermoelectric performance. In this study, single-phase Bi2−xSbxTe3.0 (x = 1.5, 1.6, and 1.7) nanocrystals without the significant inclusion of impurities were successfully synthesized through a chemical precipitation process at room temperature. The reaction rate of this process is extremely high because it is based on the charge compensation of the reactive metal ions, resulting in crystal growth suppression. The size of the Bi0.4Sb1.6Te3.0 nanocrystals was controlled from a single-nanometer scale to a submicron scale by refluxing with several organic solvents possessing different boiling points. These precursors are expected to be suitable for the preparation of bulk thermoelectric materials with controlled grain sizes.